Psychometric properties of the Malay Schizotypal Personality Questionnaire: Measurement invariance and latent mean comparisons in Malaysian adults - Barron, David; Morgan, Kevin D.; Towell, Tony; Jaafar, Jas Laile Suzana; Swami, Viren (Wiley, 2017)
Introduction: The Schizotypal Personality Questionnaire (SPQ) is a widely used self-report measurement instrument for the assessment of schizotypal personality traits. However, the factor structure of the SPQ has been a matter of some debate. As a contribution to this debate, we examined the factor structure of the SPQ in Malaysian adults. Method: A total of 382 Malaysian adults completed a Malay translation of the SPQ. Confirmatory factory analysis was used to examine the fit of 3- and 4-factor solutions for the higher-order dimensionality of the SPQ. Ethnic invariance for the best-fitting model was tested at the configural, metric, and scalar levels, and a multivariate analysis of variance was used to examine sex and ethnicity differences in domain scores. Results: The 4-factor model provided a better fit to the data than did the 3-factor model. The 4-factor model also demonstrated partial measurement invariance across ethnic groups. Latent mean comparisons for sex and ethnicity revealed a number of significant differences for both factors, but effect sizes were small. Discussion: The 4-factor structure of the SPQ received confirmatory support and can be used in Malay-speaking populations.